Comparison of Financial Performance in Health Sector Companies Listed on the Indonesia Stock Exchange before and During the Covid-19 Pandemic - Alisyah, Widya Nur; Susilowati, Lantip (Jurnal Keuangan dan Perbankan, 2022)
The trade war between China and America shocked Indonesia's economic situation towards the end of 2019, followed by a pandemic of a deadly virus known as Covid-19. It was officially revealed at the start of 2020 that the Covid-19 pandemic had infiltrated Indonesia, which directly impacted the country's economy. The weakening of the economy may impact the financial performance of different firms, including those in the health care industry. The study aims to see how the Covid-19 pandemic has affected the financial performance of healthcare enterprises listed on the Indonesian Stock Exchange. As a result, financial ratios must be examined to assess the amount of change in the company's financial performance. The researchers employed quantitative approaches and comparative research in their study. The sample for this study included 14 businesses out of 22 health sector companies listed on the Indonesia Stock Exchange. This study's data analysis is a sort of comparative analysis. The solvency ratio, liquidity ratio, and activity ratio all decreased due to the study. As a result, the profitability ratio improved. Between before the Covid-19 pandemic and after the Covid-19 pandemic struck, the company's financial performance in the health industry did not alter significantly.